2009
DOI: 10.1007/s11886-009-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Transition and transfer from pediatric to adult care of young adults with complex congenital heart disease

Abstract: Many children with complex congenital heart disease are now surviving childhood with the potential to live meaningful and productive adult lives. The process of transitioning or preparing patients and families for transfer from pediatric to adult care is challenging and rarely implemented properly. An inadequate transition process results in delayed and inappropriate care, improper timing of transfer, and undue emotional and financial stress on the patients, their families, and the health care system. At worst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 30 publications
0
41
1
Order By: Relevance
“…[11][12][13][14][15] In the current study, we demonstrate that a significant number of parents of children with moderate and complex CHD are unaware that national guidelines suggest LLCCC for their children. Such parents frequently stated that their health care team had not discussed this recommendation.…”
Section: Discussionmentioning
confidence: 67%
“…[11][12][13][14][15] In the current study, we demonstrate that a significant number of parents of children with moderate and complex CHD are unaware that national guidelines suggest LLCCC for their children. Such parents frequently stated that their health care team had not discussed this recommendation.…”
Section: Discussionmentioning
confidence: 67%
“…Across the three topics, patients identified 16‐18 years as the ideal age for health care providers to initiate discussions—in other words during the transition period from pediatric to adult care. These crucial topics of adult life should be incorporated into a comprehensive transition curriculum involving a multidisciplinary team (eg, social workers), to prepare young patients to navigate their lives with a chronic illness . “Education checklists” may be created in patient charts and reviewed on a scheduled basis or with changes in patient's education, career, health status, interest in starting a family, etc Peer support groups and informational seminars for patients and families around these topics can also be offered …”
Section: Discussionmentioning
confidence: 99%
“…24 Knauth, Verstappen, Reiss, and Webb reported that many patients have large gaps in cardiac care in their transition to adult cardiology clinics and they may never receive genetic information regarding their heart defects. 25 This again demonstrates the importance of parent education, as parents are longitudinally involved in the care of their children and can help facilitate transitions in care.…”
Section: Practice Implicationsmentioning
confidence: 95%